2019
DOI: 10.1016/j.redox.2018.101095
|View full text |Cite
|
Sign up to set email alerts
|

HSP22 suppresses diabetes-induced endothelial injury by inhibiting mitochondrial reactive oxygen species formation

Abstract: The induction of mitochondrial reactive oxygen species (mtROS) by hyperglycemia is a key event responsible for endothelial activation and injury. Heat shock protein 22 (HSP22) is a stress-inducible protein associated with cytoprotection and apoptosis inhibition. However, whether HSP22 prevents hyperglycemia-induced vascular endothelial injury remains unclear. Here, we investigated whether HSP22 protects the vascular endothelium from hyperglycemia-induced injury by reducing mtROS production. We used a high-fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 52 publications
1
35
0
Order By: Relevance
“…HSP22, a small heat shock protein, has recently been reported to have beneficial properties against oxidative stress [ 16 , 18 ], mitochondrial dysfunction [ 20 ], endothelial injury [ 19 ], aging [ 14 ] and apoptosis [ 32 ]. Concretely, an in vitro study showed that overexpression of hsp22 markedly restrained H 2 O 2 -induced hippocampal neuronal cell death by modulation of the mitochondrial-related apoptosis pathway [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSP22, a small heat shock protein, has recently been reported to have beneficial properties against oxidative stress [ 16 , 18 ], mitochondrial dysfunction [ 20 ], endothelial injury [ 19 ], aging [ 14 ] and apoptosis [ 32 ]. Concretely, an in vitro study showed that overexpression of hsp22 markedly restrained H 2 O 2 -induced hippocampal neuronal cell death by modulation of the mitochondrial-related apoptosis pathway [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock protein 22 (Hsp22), also called H11 Kinase and HSPB8, is a small heat shock protein and originally as a necessity for the growth of Drosophila melanogaster [ 14 , 15 ], has recently been demonstrated to have the properties of mitochondria-protection, anti-oxidation, anti-apoptosis in myocardial injury [ 16 ], cerebral ischemia [ 17 ] and aging [ 18 ]. Notably, hsp22 treatment could maintain the balance of mitochondrial fusion and fission to mitigate mitochondria-derived ROS [ 19 ]. Additionally, forceful proofs demonstrated that overexpression of hsp22 markedly attenuates oxidative stress-induced hippocampal neuronal cell death through the suppression of mitochondria-mediated apoptosis cascade responses [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…ATP5G3 is involved in the proton pathway and acts as an energy-driving motor (Huang et al 2013 ; He et al 2017 ; Spataru et al 2019 ). HSPB8 is known to prevent oxidative tissue damage and its expression in serum is used as a biomarker for virus induced type 1 diabetes (Karthik et al 2012 ; Li et al 2017 ; Yu et al 2019 ). We also identified rs34427781—an eQTL for several genes ( CYP2D8P, NDUFA6-AS1, CYP2D6, CCDC134, CENPM, CHADL, FAM109B, NAGA, NDUFA6, OGFRP1, OLA1P1, SEPT3, SHISA8, SLC25A5P1, SMDT1, SREBF2, TNFRSF13C, WBP2NL )—to be associated with BMI.…”
Section: Discussionmentioning
confidence: 99%
“…ATP5G3 is involved in the proton pathway and acts as an energy-driving motor (He et al, 2017; Huang et al, 2013; Spataru, Le Duc, Zagrean, & Zagrean, 2019). HSPB8 is known to prevent oxidative tissue damage and its expression in serum is used as a biomarker for virus induced type 1 diabetes (Karthik, Ilavenil, Kaleeswaran, Sunil, & Ravikumar, 2012; X. C. Li et al, 2017; L. Yu et al, 2019). We also identified rs34427781 - an eQTL for several genes ( CYP2D8P, NDUFA6-AS1, CYP2D6, CCDC134, CENPM, CHADL, FAM109B, NAGA, NDUFA6, OGFRP1, OLA1P1, SEPT3, SHISA8, SLC25A5P1, SMDT1, SREBF2, TNFRSF13C, WBP2NL ) to be associated with BMI.…”
Section: Discussionmentioning
confidence: 99%